The Karadima Case of Abuses in Chile: Contradictions of a Church Under scrutiny1 - Parker-Gumucio, C (Taylor and Francis, 2024)
The “Karadima case” stands out as one of the most emblematic incidents within the ecclesiastical abuse crisis in the Catholic Church in Chile. The exposure of allegations against the priest led to a revelation of the church’s internal workings. The manner in which the Hierarchy handled the accusations evidenced an institutional cover-up, based on networks of complicity expanding widely within the Church and beyond. This chapter seeks to dissect the repercussions that the exposure of this case has had on the Catholic Church. The Karadima scandal paved the way for an influx of complaints against other priests, subsequently garnering significant media attention. Within this backdrop, Pope Francis’ official visit was marked by tension and received a relatively muted response from the public. This scenario prompted the Vatican’s intervention, led by Pope Francis himself. It also led to the massive resignation of prelates and dealt a blow to the institution’s credibility due to its mismanagement of these allegations. The text is based on a methodology that gives priority to secondary sources - review of the mass media, interviews, and analysis of an extensive bibliography. The chapter develops a chronology of the case together with the description of the relevance of Karadima as a religious leader and the role of his followers, as well as his links with the local elite. This analysis leads us to an extensive interpretation of the impact of the Karadima case for the Catholic Church in general. © 2024 selection and editorial matter, Véronique Lecaros and Ana Lourdes Suàrez; individual chapters, the contributors.